Branding Madrasah Berbasis Adab: Membangun Citra Lembaga melalui Keunggulan Karakter Siswa - Zackyl Musthofa; Muhammad Durrin Ni’am; Moh. Mohlas; Hafidatun Nabila; Ittaqillah Haitsuma Kunta; Ida Kusumawati; Abdullah . (CV. ITTC INDONESIA, 2026)
This research is motivated by the tendency of madrasah branding which is still oriented towards promotion, publication of activities, academic achievements, and strengthening physical facilities, while the value of adab as the main characteristic of Islamic education has not been fully managed strategically as an institutional identity. This study aims to analyze the construction of adab-based madrasah branding in strengthening the image of the institution through the formation of student character as a representation of the quality of education. The research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, documentation, and open questionnaires involving madrasah heads, teachers, students, and parents. The results of the study show that adab-based branding is built through strengthening madrasah culture, teacher examples, habituating positive behavior, and consistent institutional communication. This finding confirms that a strong madrasah image is formed from the internalization of adab values that are applied systematically, sustainably, and measurably.